1976
DOI: 10.3109/inf.1976.8.issue-3.16
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-induced Nephropathy

Abstract: 162 consecutive gentamicin courses have been evaluated retrospectively with respect to nephrotoxicity of gentamicin (GM). Of these, 120 courses were administered in 106 patients for more than 2 days and under adequate control of plasma creatinine (PCr). In 62 of these 120 courses, PCr concentrations increased. In 17 courses (14%), GM therapy was found to be the only demonstrable etiology to the rise in PCr. The 17 courses with GM-induced reduction in kidney function were characterized by a prolonged duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Gentamicin nephrotoxicity appears to be related to the duration of use, the total dose administered, 14 the age of the patient, 15 and factors associated with impaired renal function. 16 With once-daily dosing, the transient high peak level does not cause toxicity. 17 Therefore, the risk of 1 or 2 doses of once-daily gentamicin is highly unlikely to cause nephrotoxicity.…”
mentioning
confidence: 99%
“…Gentamicin nephrotoxicity appears to be related to the duration of use, the total dose administered, 14 the age of the patient, 15 and factors associated with impaired renal function. 16 With once-daily dosing, the transient high peak level does not cause toxicity. 17 Therefore, the risk of 1 or 2 doses of once-daily gentamicin is highly unlikely to cause nephrotoxicity.…”
mentioning
confidence: 99%
“…Antibiotic toxicity would be expected to be equal if related to AUC [18]. If, however, aminoglycoside toxicity is related to total dose [19], the high daily dose, cystic fibrosis and leukemic patients who received up to 21.6 mg/kg/day are potentially being placed at a greater risk for toxicity than the low daily dose neonate patients who received as little as 1.5 mg/kg/day. At the same time, it is imperative that equal consideration be given to efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Only one clinical study evaluating aminoglycoside-induced nephrotoxicity has found that furosemide increases renal damage, whereas two studies have failed to find an interaction. None of these studies evaluated auditory toxicity (5,17,21). A few clinical reports have supported the association with auditory toxicity, but these studies have not included a control group and have reported small numbers of patients (8,9,11,12,14).…”
mentioning
confidence: 99%